Recent progress in flexible and stretchable piezoelectric devices for mechanical energy harvesting, sensing and actuation. (December 2016) - Dagdeviren, Canan; Joe, Pauline; Tuzman, Ozlem L.; Park, Kwi-Il; Lee, Keon Jae; Shi, Yan; Huang, Yonggang; Rogers, John A.
Abstract: Recent advances in materials science and mechanical engineering enable the realization of high performance piezoelectric systems in soft, flexible/stretchable formats, with unique opportunities for use in bio-integrated applications, from mechanical energy harvesting to sensing and actuation. This article highlights the essential mechanical to electrical conversion processes in devices and systems of this type, along with key considerations in their designs. Quantitative, experimentally validated mechanics models provide guidelines in the selection of optimized configurations and materials choices. The former focuses on thin geometries, neutral mechanical plane construction and controlled buckling. The latter includes options such as organic polymers, inorganic nanomaterials and various types of composites. Concluding sections summarize representative applications in biomedicine, ranging from devices for mechanical energy harvesting from natural motions of internal organs to sensors and actuators for the skin.